Diminished autonomic neurocardiac function in patients with generalized anxiety disorder - Kim K; Lee S; Kim JH (Neuropsychiatric Disease and Treatment)
Kyungwook Kim,1 Seul Lee,2 Jong-Hoon Kim1–3 1Gachon University School of Medicine, 2Department of Psychiatry, Gil Medical Center, Gachon University School of Medicine, Gachon University, 3Neuroscience Research Institute, Gachon University, Incheon, Republic of Korea Background: Generalized anxiety disorder (GAD) is a chronic and highly prevalent disorder that is characterized by a number of autonomic nervous system symptoms. The purpose of this study was to investigate the linear and nonlinear complexity measures of heart rate variability (HRV), measuring autonomic regulation, and to evaluate the relationship between HRV parameters and the severity of anxiety, in medication-free patients with GAD. Methods: Assessments of linear and nonlinear complexity measures of HRV were performed in 42 medication-free patients with GAD and 50 healthy control subjects. In addition, the severity of anxiety symptoms was assessed using the State-Trait Anxiety Inventory and Beck Anxiety Inventory. The values of the HRV measures of the groups were compared, and the correlations between the HRV measures and the severity of anxiety symptoms were assessed. Results: The GAD group showed significantly lower standard deviation of RR intervals and the square root of the mean squared differences of successive normal sinus intervals values compared to the control group (P<0.01). The approximate entropy value, which is a nonlinear complexity indicator, was also significantly lower in the patient group than in the control group (P<0.01). In correlation analysis, there were no significant correlations between HRV parameters and the severity of anxiety symptoms. Conclusion: The present study indicates that GAD is significantly associated with reduced HRV, suggesting that autonomic neurocardiac integrity is substantially impaired in patients with GAD. Future prospective studies are required to investigate the effects of pharmacological or non-pharmacological treatment on neuroautonomic modulation in patients with GAD. Keywords: generalized anxiety disorder, heart rate variability, parasympathetic modulation